Evaluating and ranking the factors affecting the acute pain management in older adults with dementia after hip fracture surgery: Second-order confirmatory factor analysis - Farzaneh Didvar; Fatemeh Ghaffari; Abbas Shamsalinia (Wolters Kluwer Medknow Publications, 2023)
Background: Even though nurses take various measures to decrease acute pain after surgery in older adults with dementia, it is unclear why most of them suffer from severe pain. This study aimed to evaluate the factors affecting acute pain management in older adults with dementia after hip fracture surgery. Materials and Methods: This cross-sectional study used single-stage cluster and convenience sampling to select 330 nurses working in hospitals located in Western Mazandaran, Iran, in 2020. The demographic characteristic questionnaire and the Obstacles to Postoperative Pain Management in Dementia Scale (OPOPMDS) were used to collect data. Results: The study results confirmed the modified model. The second-order Confirmatory Factor Analysis (CFA) indicated that the Critical Ratio (CR) for all three factors was more than 1.96, and the significance level was considered 0.05. Based on the values of standard coefficients, older people-related (β = 0.86, p < 0.001), system-related (β = 0.70, p < 0.001), and healthcare provider-related (β = 0.61, p < 0.001) factors had the highest impacts on the OPOPMD. Conclusions: The study results suggested that older adult-related factors had the most significant impact on the OPOPMD.